Synthesis, physical and chemical properties of esters of 2-((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triazole-3-yl)thio)ethanoic and 3-(((5-(hydroxy(phenyl)methyl)-4-R-1,2,4-triazole-3-yl)thio)methyl)benzoic acids - А. M. Rud; A. G. Kaplaushenko; Yu. M. Kucheryavyi; Fadi Al Zedan (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The wide use of 1,2,4-triazole derivatives in medical practice is primarily explained by two most important properties: high biological activity and low toxicity. It is difficult to overestimate the contribution to medical practice, which such medicines as posaconazole and letrozole have made. Many scientists of the pharmaceutical industry pay attention to the search of biologically active substances among this heterocyclic system derivatives.